2020
DOI: 10.1101/2020.02.07.939256
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autism-linked Cullin3 germline haploinsufficiency impacts cytoskeletal dynamics and cortical neurogenesis through RhoA signaling

Abstract: E3-ubiquitin ligase Cullin3 (Cul3) is a high confidence risk gene for Neurodevelopmental Disorders (NDD) including Autism Spectrum Disorder (ASD) and Developmental Delay (DD). We generated haploinsufficient Cul3 mouse model to investigate brain anatomy, behavior, molecular, cellular, and circuit-level mechanisms dysregulated by Cul3 mutations. Brain MRI of Cul3 mutant animals found profound abnormalities in half of brain regions, including decreased volume of cortical regions and increased volume of subcortica… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Previous research has highlighted the crucial role of Cul3 in diseases such as breast ( 21) and ovarian cancer (22). However, recent studies have demonstrated its involvement in central nervous system (CNS) diseases, particularly (NDDs) (23)(24)(25)(26).…”
Section: Cul3 Expression In the Central Nervous Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research has highlighted the crucial role of Cul3 in diseases such as breast ( 21) and ovarian cancer (22). However, recent studies have demonstrated its involvement in central nervous system (CNS) diseases, particularly (NDDs) (23)(24)(25)(26).…”
Section: Cul3 Expression In the Central Nervous Systemmentioning
confidence: 99%
“…To investigate the effects of Cul3 mutations on brain development, Amar et al (23) employed CRISPR/Cas9 genome engineering technology to create a whole-brain Cul3-KO mouse (Cul3 +/− )(Table 2; Figure 3). They introduced a 1-bp frameshift insertion into Cul3 exon 6, which is one base pair upstream of the mutated nucleotide in ASD patients, thereby establishing a Cul3 +/− haploinsufficiency mouse model on a C57BL/6 N background (9,23). Cul3 +/− mice displayed social and cognitive deficits, as well as hyperactivity, accompanied by reduced dendritic growth and cortical neuronal activity.…”
Section: Whole-brain Cul3-komentioning
confidence: 99%
See 3 more Smart Citations